Hyperoxia attenuated nitrotyrosine concentration in the lung tissue of rats with experimental pneumonia - Fisárková, B; Vytásek, R; Miková, D; Vízek, M (Physiological research, 2004)
Although nitrated proteins have been repeatedly used as markers of lung injury, little is known about their formation and metabolism under hyperoxia. We therefore measured 3-nitrotyrosine (3NTYR) concentrations in lung tissue and serum of rats with carrageenan-induced pneumonia exposed to hyperoxia. Twenty-nine Wistar male rats were assigned to one of 4 groups. Two experimental groups were treated by intratracheal application of carrageenan (0.5 ml of 0.7 % solution) and then one was exposed to hyperoxia for 7 days (FIO2 0.8), the other to air. Rats of two control groups breathed either hyperoxic gas mixture or air for 7 days. At the end of exposure the ventilation was determined in anesthetized, intubated animals in which 3NTYR concentrations were measured in the lung tissue and nitrites and nitrates (NOx) were estimated in the serum. Carrageenan instillation increased 3NTYR concentrations in lung tissue (carrageenan-normoxic group 147+/-7 pmol/g protein, control 90+/-10 pmol/g protein) and NOx concentration in the serum (carrageenan-normoxic group 126+/-13 ppb, control 78+/-9 ppb). Hyperoxia had no effect on lung tissue 3NTYR concentration in controls (control-hyperoxic 100+/-14 pmol/g protein) but blocked the increase of lung tissue 3NTYR in carrageenan-treated rats (carrageenan-hyperoxic 82+/-13 pmol/g protein), increased NOx in serum (control-hyperoxic 127+/-19 ppb) and decreased serum concentration of 3NTYR in both hyperoxic groups (carrageenan-hyperoxic 51+/-5 pmol/g protein, control-hyperoxic 67+/-7 pmol/g protein, carrageenan-normoxic 82+/-9 pmol/g protein, control 91+/-7 pmol/g protein). The results suggest that hyperoxia affects nitration of tyrosine residues, probably by increasing 3NTYR degradation.
Keywords: potkani Wistar; Rats; pneumonie; tyrosin; Hyperoxia; Lung; Animals; hyperoxie; krysa rodu Rattus; Pneumonia; mužské pohlaví; Male; Rats, Wistar; karagenan; zvířata; Tyrosine; plíce; Carrageenan